The Political Phenomenology of Gender Roles in Security Agencies: The Ghana Armed Forces in Perspective - Manu, E. P. (University of Ghana, 2024)
This study investigates the experiences of female personnel within the Ghana Armed Forces (GAF), focusing on how they negotiate their professional identities and challenge traditional gender norms. Guided by the Psychopolitics of Consciousness and Social Constructivism theories, the research explores the intersection of gender dynamics and military culture. Through qualitative analysis, the study examines official GAF pronouncements, training manuals, and leadership discourses, highlighting the pervasive influence of traditional gender norms and the mechanisms through which they are perpetuated. The findings reveal that female personnel within the GAF navigate a complex landscape where institutional structures and societal expectations shape their professional experiences. Despite facing significant barriers and gender biases, these women exhibit agency and reflexivity in challenging hegemonic discourses and asserting their competence and leadership capabilities. The study uncovers the persistence of gender-based challenges, such as skepticism and discrimination from male colleagues, and highlights the limitations of individual agency in overcoming entrenched power dynamics. Furthermore, the research identifies context-specific nuances unique to the Ghanaian military environment, emphasizing the influence of broader societal norms and cultural expectations on the construction of gender identities. The experiences of female personnel reflect both the resistance against and the negotiation with traditional gender norms, contributing to a deeper understanding of gender dynamics within military institutions. Overall, this study underscores the need for comprehensive institutional reforms and cultural shifts to promote gender equality and inclusivity within the GAF. It calls for targeted interventions that address systemic gender inequalities and support the empowerment of female personnel in military settings. By providing valuable insights into the experiences of women in the GAF, this research contributes to the broader discourse on gender and military culture, informing efforts to create more equitable and inclusive Armed Forces
PhD. Political Science
Keywords: Ghana Armed Forces (GAF); female; Political